2009
DOI: 10.3168/jds.2009-2241
|View full text |Cite
|
Sign up to set email alerts
|

Inulin-enriched dairy desserts: Physicochemical and sensory aspects

Abstract: The aim of this work was to study how adding inulin of different average chain lengths (long-chain, native, and short-chain inulin) at a concentration of 7.5% (wt/wt) would affect the physicochemical and sensory characteristics of starch-based dairy desserts formulated with either skim or whole milk. The results have shown that the effect of adding 7.5% inulin of different average chain length can give rise to products with different rheological behavior and different sensory characteristics. The skim milk sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 28 publications
5
46
0
2
Order By: Relevance
“…As a consequence of inulin aggregation, the rheological properties of the custard changed showing an important increase in consistency, thixotropy and elasticity. Furthermore, the presence of these particles could be responsible for an increase in the sensation of roughness, as observed in a previous work for this type of system (Gonzalez-Tomas et al, 2009).…”
Section: Introductionsupporting
confidence: 71%
“…As a consequence of inulin aggregation, the rheological properties of the custard changed showing an important increase in consistency, thixotropy and elasticity. Furthermore, the presence of these particles could be responsible for an increase in the sensation of roughness, as observed in a previous work for this type of system (Gonzalez-Tomas et al, 2009).…”
Section: Introductionsupporting
confidence: 71%
“…An increase in solids was expected as the prebiotic contains additional glucose, fructose and sucrose (<14%). Similar findings were reported by Gonza´lez-Toma´s et al (2009) for dairy desserts, with control samples shown to be lower than inulin-enriched samples. No storage effects on the soluble solids content were observed for both controls and prebiotic-enriched ready-desserts.…”
Section: Physicochemical Propertiessupporting
confidence: 88%
“…Therefore, a direct comparison with other studies is difficult. However, Gonza´lez-Toma´s et al (2009) observed higher L* values (p < 0.05) for control samples (without inulin) compared to inulin-enriched (short chained at inclusion level of 7.5% w/w) dairy desserts, while Guven et al (2005) reported increasing the levels (1-3% w/w) of inulin negatively affected the colour and appearance scores of visually assessed yoghurt Table 2. Food Science and Technology International 18 (2) compared to controls (no inulin inclusion).…”
Section: Sensory Acceptabilitymentioning
confidence: 94%
“…While the prebiotic effects of both inulin and oligofructose have been widely reported in dairy products (Cardarelli et al, 2008;Gonzàlez-Tomàs et al, 2009), their performance in an acidic environment such as an apple puree, is undetermined. Furthermore, the stability of inulin based prebiotics subjected to high pressure conditions and sustained thermal pasteurisation temperatures is also unclear.…”
Section: Introductionmentioning
confidence: 99%